The Effect of the Second-Order Wave Loads on Drift Motion of a Semi-Submersible Floating Offshore Wind Turbine - Thanh-Dam Pham; Hyunkyoung Shin (Journal of Marine Science and Engineering, 2020)
Floating offshore wind turbines (FOWTs) have been installed in Europe and Japan with relatively modern technology. The installation of floating wind farms in deep water is recommended because the wind speed is stronger and more stable. The design of the FOWT must ensure it is able to withstand complex environmental conditions including wind, wave, current, and performance of the wind turbine. It needs simulation tools with fully integrated hydrodynamic-servo-elastic modeling capabilities for the floating offshore wind turbines. Most of the numerical simulation approaches consider only first-order hydrodynamic loads; however, the second-order hydrodynamic loads have an effect on a floating platform which is moored by a catenary mooring system. At the difference-frequencies of the incident wave components, the drift motion of a FOWT system is able to have large oscillation around its natural frequency. This paper presents the effects of second-order wave loads to the drift motion of a semi-submersible type. This work also aimed to validate the hydrodynamic model of Ulsan University (UOU) in-house codes through numerical simulations and model tests. The NREL FAST code was used for the fully coupled simulation, and in-house codes of UOU generates hydrodynamic coefficients as the input for the FAST code. The model test was performed in the water tank of UOU.